Short Communication: Rhizoctonia-like fungi isolated from roots of Dendrobium lancifolium var. papuanum and Calanthe triplicata in Papua, Indonesia (Biodiversitas Journal of Biological Diversity, 2016)
Agustini V, Sufaati S, Suharno, Suwannasai N. 2016. Rhizoctonia-like fungi isolated from roots of Dendrobium lancifoliumÂ var. papuanum and Calanthe triplicata in Papua, Indonesia. Biodiversitas 17: 377-383. The aim of this study was to isolate and identifyRhizoctonia-like fungi associated with the roots of the terrestrial orchids Dendrobium lancifolium A. Rich var. papuanum and CalantheÂ triplicata (Willem) Ames in Papua. The fungi were isolated from the transversal section of the orchid roots. Two isolates have been morphologically identified as genus Rhizoctonia. Further identification was carried out based on the analysis of nucleotide sequences generated from ITS and 28S rDNA. The results revealed that both isolates closed to Ceratobasidium sp. and the phylogenetic analysis confirmed that they were determined as Rhizoctonia-like fungi.